Neutrally Buoyant Particle Migration in Poiseuille Flow Driven by Pulsatile Velocity - Lizhong Huang (Micromachines, 2021)
A neutrally buoyant circular particle migration in two-dimensional (2D) Poiseuille channel flow driven by pulsatile velocity is numerical studied by using immersed boundary-lattice Boltzmann method (IB-LBM). The effects of Reynolds number (<semantics>25≤Re≤200</semantics>) and blockage ratio <semantics>(0.15≤k≤0.40)</semantics> on particle migration driven by pulsatile and non-pulsatile velocity are all numerically investigated for comparison. The results show that, different from non-pulsatile cases, the particle will migrate back to channel centerline with underdamped oscillation during the time period with zero-velocity in pulsatile cases. The maximum lateral travel distance of the particle in one cycle of periodic motion will increase with increasing <semantics>Re</semantics>, while <semantics>k</semantics> has little impact. The quasi frequency of such oscillation has almost no business with <semantics>Re</semantics> and <semantics>k</semantics>. Moreover, <semantics>Re</semantics> plays an essential role in the damping ratio. Pulsatile flow field is ubiquitous in aorta and other arteries. This article is conducive to understanding nanoparticle migration in those arteries.